Minimum Completeness Criteria for Islamic Education Subjects - Jannah, Mishul; Muslimah, Muslimah (CV. Creative Tugu Pena, 2021)
This article aims to determine the Minimum Completeness Criteria by the education unit by considering the characteristics of the basic competencies to be achieved, the carrying capacity, and the characteristics of students. The Minimum Criteria of Mastery Learning. is a joint reference for educators, students, and students' parents. in this article discusses the Minimum Criteria of Mastery Learning. This article is written with a qualitative approach and uses literature methods. And the results of this article are: Minimum Criteria of Mastery Learning is the lowest standard that must be achieved by every student through Teaching and Learning Activities (TLA) or the minimum limit of student achievement in the competence of each indicator, basic competence, and standard competency aspects of subject assessment that must be mastered. Determination of the the Minimum Criteria of Mastery Learning value is carried out through an analysis of minimum learning completeness on each indicator by taking into account the complexity, carrying capacity and intake of students to achieve completeness of basic competencies and competency standards. Keywords: Minimum Completeness Criteria, Islamic Education Subject, Kriteria Ketuntasan Minimum